POLICY EVALUATION OF EMPOWERMENT OF COASTAL POOR COMMUNITIES THROUGH INTEGRATED PEOPLE'S SALT BUSINESS DEVELOPMENT WITH GEOMEMBRANE TECHNOLOGY IN 2018-2019 (Study in North Aceh District) - Saharuddin; Endang Larasati; Sri Suwitri; Ida Hayu Dwimawanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Indonesia is an archipelagic country surrounded by oceans. Aceh is the westernmost province of Indonesian territory. A number of districts are located on the coast of the Indian Ocean, most of the population lives in coastal areas. When viewed from the perspective of their livelihood, they are included in the category of poor people. The average livelihood of them is as a farmer and fisherman. Development of the People's Salt Business (PUGAR) as a national program was made with the aim of increasing the welfare of the Indonesian people, especially salt farmers. The purpose of this study was to evaluate the Empowerment Policy for the Coastal Poor through the Development of Integrated People's Salt Businesses with Geo-Membrane Technology in North Aceh District, the constraints and obstacles in implementing the policy. This study used a descriptive research method with a qualitative approach, technical data collection was carried out through interviews, observation, and documentation. The research findings were evaluated using William N. Dunn's policy evaluation theory with 3 (three) evaluation criteria, namely Effectiveness, Efficiency and Responsiveness. The results of the study show that the evaluation of the policy of developing people's salt businesses in Aceh district is the government's effort to empower poor communities in coastal areas to improve their welfare through the provision of facilities and infrastructure, land integration and salt business institutions (KUGaR). The aspect of duties and authority shows that it is dominated by the Maritime Affairs and Fisheries Service, while the technical team is more on the number of team personalities for fulfilling procedures only. Many technical tasks are carried out in Marine and fisheries. In addition, the technical team has not implemented its capacity according to the main duties and functions of the SKPD. Meanwhile PUGaR is comprehensive in nature covering all aspects of people's lives, including education, health and economic endeavors. Aspects of the distribution of aid for facilities and infrastructure and disbursement of the budget have been carried out optimally. While the tasks and functions of institutions (cooperatives) have not been able to motivate people to join salt business groups under the auspices of cooperatives, this shows that institutionally cooperatives have not made a significant contribution in increasing people's salt businesses. The resource aspect shows that the involvement of human resources in general in the development of the people's salt business has shown adequate results, but in terms of quality it is not optimal both at the group level and at the management institutional level. While the aspects of facilities and infrastructure and budgeting look quite convincing in accordance with the needs for developing the potential of the salt business.